Simple measure for power transfer efficiency of coupled dipole antennas based on root-mean square value of transient current. (March 2023) - Poljak, D.; Antonijevic, S.
Asbtract: The paper deals with a novel measure for power transfer efficiency (PTE) simply defined as a ratio of squared root-mean values (RMS) of current at the input of received and transmitted wire antenna, respectively (instead of exploiting commonly used definitions that use ratio of received and transmitted power, respectively), stemming from the time domain analysis of wire antennas of finite length. Instead of widely used approximate approach using the circuit theory in the frequency domain, this paper uses the most rigorous approach in classical electrodynamics based on the full-wave model in the time domain, thus considering wireless power transfer (WPT) between two coupled dipole antennas in free space, one wire active (driven at its center with impulsive voltage source) and the passive wire (loaded with concentrated resistance). The space-time dependent currents along the wires, as a basis of time domain analysis, are obtained by numerically solving the set of coupled Hallen integral equations. The transient currents obtained with the direct time domain approach are compared against results obtained via indirect approach combining NEC (Numerical Electromagnetic Code) and Inverse Fast Fourier Transform (IFFT). Once the current distribution has been determined, it is possible to calculate the charge distribution using the continuity equation. Knowing the space-time distribution of current and charge along dipoles, time domain (TD) energy measures involving spatial integrals of squared values of transient current and charge, pertaining to the energy stored in the electric and magnetic field, respectively, of dipoles are evaluated. Finally, according to definition stemming from the circuit theory, the distribution of root-mean-square (RMS) values of transient currents are calculated and corresponding PTE measure is obtained.